Urbanization, Industrialization and Inequalities in Africa: does threshold matter? - ONGO NKOA, Bruno Emmanuel; ZOGO EKASSI, Richard; Song, Jaques Simon (International Journal of Scientific Research and Management (IJSRM), 2021)
This paper examines the impact of urbanization and industrialization on observed inequalities in a sample of 48 African countries. We specify and estimate a panel data model using the Generalized Method of Moments-System (GMM-S) over the period 1980-2016 along the different dimensions of inequality. Our results show that urbanization increases income, environmental and housing inequalities in Africa, while industrialization reduces them. Our results remain robust with the use of Panel Smooth Transition Regression Model (PSTR) and Panel Transition Regression Model (PTR). We suggest taking into account the disparities identified in the inclusive urbanization and industrialization policies of African cities.